Fundusze polityki strukturalnej w realizacji polityki spójności Unii Europejskiej w Polsce ze szczególnym uwzględnieniem Dolnego Śląska - Rymarczyk, Jan (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The main goal of the cohesion policy of the European Community is to decrease the disproportions of the development of its regions. The most important instruments of this policy are The Structural Funds and The Fund of Cohesion. The European Union decided to divide its financial assistance for Poland into three periods. The first period was before the Polish access to the EU, the second concerned the years of 2004-2006 an the third will take the years of 2007-2013. The last period will be the most important because of the high level of the finance. Their effective use should contribute to the significant development of the country and particularly the region of Lower Silesia. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (16); 2008; nr 1193, s. 309-319